Mapping Protein-Specific Micro-Environments in Live Cells by Fluorescence Lifetime Imaging of a Hybrid Genetic-Chemical Molecular Rotor Tag - Gatzogiannis, Evangelos (2012)
The micro-viscosity and molecular crowding experienced by specific proteins can regulate dynamics and function within live cells. Taking advantage of the emerging TMP-tag technology, we present the design, synthesis and application of a hybrid genetic-chemical molecular rotor probe whose fluorescence lifetime can report on protein-specific micro-environments in live cells.